HUMOR IN DEDDY’S CORBUZIER “SOMASI” - Flores, Priskalia D; Padji, Simon S; Sama, Gratiana (Lantern: Journal of Language and Literature, 2024)
The purpose of this study was to find out the forms of humor in a stand-up comedy video titled "Somasi". It used the humor theory proposed by Martin to support this analysis. This study used the descriptive-qualitative method. The results of this study showed that the comics' utterances contain several forms of humor. These types include jokes, spontaneous conversational humor consisting of sarcasm, satire, overstatement and understatement, self-deprecation, ridicule, answers to rhetorical questions, and clever answers to serious statements.